Evaluasi Kesesuaian Lahan untuk Tanaman Jagung di Kecamatan Bukit Sundi, Kabupaten Solok - Agustin, Puja Yulmi; Febriandi, Febriandi (TSAQOFAH, 2025)
This study aims to assess the production potential and land suitability level for maize cultivation in Bukit Sundi Subdistrict, in light of the significant decline in maize production over the past five years despite the area's dominance in the agricultural and plantation sectors. The research employed a quantitative descriptive approach using secondary data covering the entire Bukit Sundi Subdistrict. Sample determination was based on maize growth requirement parameters to evaluate land suitability. The results show that maize production in 2023 reached 107.3 tons with a productivity rate of 8.25 tons/ha, indicating good development potential compared to previous years. Land suitability evaluation using the fuzzy logic method revealed that land in Bukit Sundi Subdistrict falls into two categories: highly suitable and moderately suitable. Highly suitable land dominates with an area of 3,895.9 ha, while moderately suitable land covers 1,674.56 ha. These findings indicate that Bukit Sundi Subdistrict holds strong potential for maize development, provided that land is utilized optimally and agricultural management is carried out sustainably.